2021
DOI: 10.1155/2021/6633845
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Distribution Width and Mortality in Hemodialysis Patients

Abstract: Objectives. The association between platelet distribution width (PDW) and mortality in hemodialysis (HD) patients has received little attention. Methods. We retrospectively enrolled HD patients in a single center from January 1, 2008, to December 30, 2011. The primary and secondary endpoints were all-cause and cardiovascular mortality, respectively. The association between PDW and mortality was estimated by Cox regression model. Results. Of 496 patients, the mean age was 52.5 ± 16.6 years, and the Charlson com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…PDW is a specific marker reflecting platelet activity [ 6 ]. It was shown that a large PDW value indicated a large reticulated platelet volume and high metabolic activity [ 5 ]. A high platelet activity means that the platelets can strongly promote inflammation and coagulation that are closely related to CVD [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PDW is a specific marker reflecting platelet activity [ 6 ]. It was shown that a large PDW value indicated a large reticulated platelet volume and high metabolic activity [ 5 ]. A high platelet activity means that the platelets can strongly promote inflammation and coagulation that are closely related to CVD [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study of 1557 PD patients revealed that PDW > 13.2 fL was associated with the incidence of new-onset CVD in PD patients [ 12 ]. In one study of HD patients, it was shown that PDW ≥ 16.31% was independently associated with a high risk of all-cause and cardiovascular deaths [ 5 ]. Yu et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been conducted with PDW in many clinical conditions related to the kidney. Ruijan et al showed that PDW is associated with cardiovascular and all-cause mortality in patients treated with hemodialysis [24]. In a study of Yu et al, PDW was shown to be a marker for predicting lupus nephritis [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a predictive model for AAAD, Wang et.al ( 19 ) displayed that PDW was an independent factor in predicting in-hospital death (hazard ratio: 3.755, 95% CI: 1.436–9.815, P < 0.001). A retrospective cohort found that high PDW values (≥16.31%) were independently associated with higher risk of all-cause (hazard ratio: 1.49, 95% CI: 1.15–6.82) and cardiovascular deaths (hazard ratio: 2.26, 95% CI: 1.44–3.63) in hemodialysis patients ( 20 ). Regarding to acute myocardial infarction treated with primary percutaneous coronary intervention, Rechciński et al ( 6 ) observed higher PDW values (≥16 fL) correlated with a higher mortality rate when compared with PDW < 16 fL (17.4 vs. 6.3%, P = 0.001) in a sample of 538 patients.…”
Section: Discussionmentioning
confidence: 99%